2011
DOI: 10.1124/dmd.111.039461
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Screening of Cytochrome P450 BM3 Mutants for Their Metabolic Activity and Diversity toward a Wide Set of Drug-Like Molecules in Chemical Space

Abstract: ABSTRACT:In the present study, the diversity of a library of drug-metabolizing bacterial cytochrome P450 (P450) BM3 mutants was evaluated by a liquid chromatography-mass spectrometry (LC-MS)-based screening method. A strategy was designed to identify a minimal set of BM3 mutants that displays differences in regio-and stereoselectivities and is suitable to metabolize a large fraction of drug chemistry space. We first screened the activities of six structurally diverse BM3 mutants toward a library of 43 marketed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 38 publications
(40 reference statements)
4
59
0
Order By: Relevance
“…This progress can directly be of use for efficient and timesaving production of human drug metabolites. High yields and conversion rates can already be achieved by using corresponding human (Rushmore et al, 2000;Vail et al, 2005;Schroer et al, 2010;Geier et al, 2012;Schiffer et al, 2015) or suitable nonhuman (Taylor et al, 1999;Otey et al, 2006;Sawayama et al, 2009;Reinen et al, 2011;Di Nardo and Gilardi, 2012;Kiss et al, 2015;Ren et al, 2015) P450 enzymes in a whole-cell system to produce respective metabolites. The majority of published bacterial P450 enzymes used for the conversion of drugs are mutants of CYP102A1 (BM3) from Bacillus megaterium.…”
Section: Discussionmentioning
confidence: 99%
“…This progress can directly be of use for efficient and timesaving production of human drug metabolites. High yields and conversion rates can already be achieved by using corresponding human (Rushmore et al, 2000;Vail et al, 2005;Schroer et al, 2010;Geier et al, 2012;Schiffer et al, 2015) or suitable nonhuman (Taylor et al, 1999;Otey et al, 2006;Sawayama et al, 2009;Reinen et al, 2011;Di Nardo and Gilardi, 2012;Kiss et al, 2015;Ren et al, 2015) P450 enzymes in a whole-cell system to produce respective metabolites. The majority of published bacterial P450 enzymes used for the conversion of drugs are mutants of CYP102A1 (BM3) from Bacillus megaterium.…”
Section: Discussionmentioning
confidence: 99%
“…Positions which were selected for mutagenesis were residues 72, 74, 82, 87 and 437 which appear to be key active site residues and have profound influence on regio-and stereoselectivity of P450 BM3 mutants. 20,22,28,29 …”
Section: Selection Of P450 Bm3 Variantsmentioning
confidence: 98%
“…18 Recent studies have reported the ability of cytochrome P450 BM3 mutants to produce human relevant drug metabolites of several drugs including NSAIDs. [19][20][21] Engineered P450 BM3 mediated hydroxylation of NSAIDs like diclofenac, ibuprofen and naproxen have been reported. [22][23][24][25] In the present study, fenamic acid NSAIDs (Figure 1) have been used as examples to demonstrate the ability of P450 BM3 mutants to produce human relevant metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The direct use of human cytochrome P450 is limited by the need of a redox partner and the poor stability and activity. However, bacterial counterparts such as cytochrome P450 BM3 (CYP102A1) from Bacillus megaterium, can be directly used [3] or engineered to metabolise drugs and to produce the same metabolites as the human enzymes [4][5][6][7][8][9][10][11][12][13][14]. This protein is a selfsufficient fatty acids monoxygenase containing a NADPH-dependent reductase (BMR) and a P450 catalytic domain (BMP) fused in a single polypeptidic chain [15,16].…”
Section: Introductionmentioning
confidence: 99%